# Introduction

Most programmers probably already know this, but for beginner programmers, it is quite frequently unknown or overlooked.

When you evaluate expressions you need not evaluate "If <expression> = true then", you simply evaluate "If <expression> then"

This is because <expression> already produces a Boolean value, and an if then branch breaks down to the following logic:

`1.``If` `<Expression> then`
`2.``    ``'True was the case`
`3.``Else`
`4.``    ````'False was the case```
`5.``End` `If`

So when you evaluate the following expression for example:

(1+2 = 4)

This will automatically become false, because 1+2 does not equal 4.

True will always = true (It is what it is!)

False will always = false(It is what it is!)

Which means that saying:

`1.``If` `(1+2=4) = true then`
`2.``    ``'True was the case`
`3.``Else`
`4.``    ````'False was the case```
`5.``End` `If`

is effectively saying the same as saying

`1.``If` `<``Boolean``> = true then`
`2.````2.    ````'True was the case`
`3.``3.``Else`
`4.````4.    ````'False was the case`
`5.``5.``End` `If`

But since a Boolean "is what is", we need not check if "<Boolean>" = true...

So the following is the same as above:

`1.``If` `<``Boolean``> then`
`2.``    ``'True was the case`
`3.``Else`
`4.``    ````'False was the case```
`5.``End` `If`

And the following is just as absurd as evaluating true in an expression:

`1.``If` `(((((1 + 2) = 3) = ``True````) = ````True````) = ````True````) ````Then`
`2.``    ``'True was the case`
`3.``Else`
`4.``    ````'False was the case```
`5.``End` `If`

In conclusion, try to remember, "It is what it is."